Measuring teachers’ competencies for a purposeful use of augmented reality experiments in physics lessons - Freese, Mareike; Teichrew, Albert; Winkelmann, Jan; Erb, Roger; Ullrich, Mark; Tremmel, Michael (Frontiers in Education, 2023)
Nowadays, teachers are facing a more and more digitized world, as digital tools are being used by their students on a daily basis. This requires digital competencies in order to react in a professional manner to individual and societal challenges and to teach the students a purposeful use of those tools. Regarding the subject (e.g., STEM), this purpose includes specific content aspects, like data processing, or modeling and simulations of complex scientific phenomena. Yet, both pre-service and experienced teachers often consider their digital teaching competencies insufficient and wish for guidance in this field. Especially regarding immersive tools like augmented reality (AR), they do not have a lot of experience, although their willingness to use those modern tools in their lessons is high. The digital tool AR can target another problem in science lessons: students and teachers often have difficulties with understanding and creating scientific models. However, these are a main part of the scientific way of acquiring knowledge and are therefore embedded in curricula. With AR, virtual visualizations of model aspects can be superimposed on real experimental backgrounds in real time. It can help link models and experiments, which usually are not part of the same lesson and are perceived differently by students. Within the project diMEx (digital competencies in modeling and experimenting), a continuing professional development (CPD) for physics teachers was planned and conducted. Secondary school physics educators were guided in using AR in their lessons and their digital and modeling competencies for a purposeful use of AR experiments were promoted. To measure those competencies, various instruments with mixed methods were developed and evaluated. Among others, the teachers’ digital competencies have been assessed by four experts with an evaluation matrix based on the TPACK model. Technological, technical and design aspects as well as the didactical use of an AR experiment were assessed. The teachers generally demonstrate a high level of competency, especially in the first-mentioned aspects, and have successfully implemented their learnings from the CPD in the (re)design of their AR experiments.